Traditional Male Role Norms and Sexual Prejudice in Sport Organizations: A Focus on Italian Sport Directors and Coaches - Anna Lisa Amodeo; Sabrina Antuoni; Manuela Claysset; Concetta Esposito (Social Sciences, 2020)
Despite the common belief that sport is an excellent instrument to promote social inclusion, distal minority stressors, such as homophobic slurs and insulting or degrading comments, are frequently reported in sport contexts. The aim of this contribution was to expand previous knowledge on negative attitudes toward sexual minorities (gay and lesbian people) in sport-related contexts, by examining how staff employed in organizational sport contexts scored on three different dimensions of sexual prejudice toward sexual minority athletes: open rejection (i.e., blatant prejudice), denial of visibility (i.e., negative attitudes toward the coming out), and gendering performance (i.e., gender stereotypes about sport performance and skills). Furthermore, we examined the relationship between traditional norms of masculinity and dimensions of sexual prejudice. The sample consisted of 178 Italian sport directors and coaches who were asked to complete an online survey (70 women and 108 men, mostly aged from 38 to 65 years old). A repeated-measures ANOVA revealed that participants scored higher on denial of visibility, with respect to open rejection and gendering performance, independently of gender and sport role. The structural equation model showed that endorsing traditional male role norms was significantly associated with open rejection and gendering performance, whereas no significant association was found with denial of visibility. The findings provide further evidence that sexual prejudice is prevalent in sport organizations, supporting the importance of raising awareness among sports personnel about prejudiced beliefs that may lead minority people to experience severe stress-inducing situations.